2020
DOI: 10.5671/ca.44.3.7
|View full text |Cite
|
Sign up to set email alerts
|

Dabigatran Use Associated with Hemopericardium and Hemothorax

Abstract: Concurrent spontaneous hemopericardium and hemothorax due to anticoagulant use are extremely rare in clinical practice. Dabigatran is an oral direct thrombin inhibitor approved to prevent stroke or thromboembolic episodes in patients with nonvalvular atrial fibrillation. We report the case of a 73-year-old man who received dabigatran therapy (150 mg twice a day) for 3 months and developed massive spontaneous hemothorax and hemopericardium associated with fever. Emergency chest computed tomography scan establis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
0
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 13 publications
(20 citation statements)
references
References 0 publications
0
12
0
1
Order By: Relevance
“…Winners, therefore, hit more Wn than losers and, therefore, it can be concluded that aggressive play and taking the initiative in the game has a positive influence in tennis results. 22,23 As per differences by team (winner and loser) and surface in absolute values, at Roland Garros more Wn were observed in WT than in LT. More UE in WT were also observed at the Australian Open (18.7) than in Wimbledon (8.3).…”
Section: Point Endingmentioning
confidence: 96%
See 1 more Smart Citation
“…Winners, therefore, hit more Wn than losers and, therefore, it can be concluded that aggressive play and taking the initiative in the game has a positive influence in tennis results. 22,23 As per differences by team (winner and loser) and surface in absolute values, at Roland Garros more Wn were observed in WT than in LT. More UE in WT were also observed at the Australian Open (18.7) than in Wimbledon (8.3).…”
Section: Point Endingmentioning
confidence: 96%
“…20 To the authors knowledge, there is only one previous study that analysed the point ending and the structure of the professional doubles game and, moreover, it studied the men's game, 4 and only another previous study that analysed the women's professional doubles game. 20 As per the singles game, there are several studies that have analysed winners (Wn) and errors, and some of them related them to the players' style of play and the probability of winning or losing matches, [21][22][23] as well as to the time spent in different zones of the court. 24 As it can be concluded, there is no previous literature that have analysed the variables that describe the structure of matches and the way in which points are finished in women's doubles.…”
Section: Introductionmentioning
confidence: 99%
“…The MT as well as AT and CT were basically shorter among boys than girls from preschool to high school ages (Table 1). Sex differences in motor performance have often been investigated (Barnett et al, 2016;Katić et al, 2013;Kokštejn et al, 2017;Latorre-Román et al, 2016;Morris et al, 1982). In general, boys performed better in object movement while girls performed better in self-movement (Wälti et al, 2022).…”
Section: Sex Differencesmentioning
confidence: 99%
“…Agility is defined as a rapid whole-body movement with a change of velocity or direction in response to a stimulus, involving adjustments to ongoing actions, changes of speed, changes of direction, and/or reacting to a given stimulus (Sheppard & Young, 2006). For example, Katić et al (2013), focusing on children aged 11-14 years old, reported that stepping laterally, doing an obstacle course backward, and the 20-m dash were superior in boys than girls. The motor task used in this study was different from the above-mentioned previous studies, but the motor ability reflected by CTJ may be greater in boys than girls.…”
Section: Sex Differencesmentioning
confidence: 99%
See 1 more Smart Citation